Senior cohousing as a housing and existential solution: from Denmark to Spain - Vivas Tesón, Inmaculada (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The co-housing model known as cohousing is not new, but it is recent in Spain, where it is expected to expand significantly in the coming years. In cohousing, a group of people come together to live together around a common, self-managed living project. They are collaborative housing communities for all ages and profiles, although most of the existing projects currently focus on senior citizens. The numerous advantages of senior cohousing, as well as its legal framework in Spanish private law, are analysed in this paper.